IMPLEMENTATION OF PENTAHELIX IN SYNERGY ACCELERATION OF COVID HANDLING 19 - Eki Baihaki; Henni Gusfa; Riza Gusti Rahayu (LPM Universitas Pasundan, 2020)
The world experienced chaos caused by the Covid-19 virus which spread and caused death. Covid-19 causes paralysis in various sectors of life as a nation and state. But what is even more concerning is that there are still sectoral egos on a micro and macro scale in their handling. The research objective is to implement cross-institutional communication synergy (Phentahelix) in accelerating the handling of Covid-19. The method used in the Cimahi case study relies on handling Covid-19 from the lowest organizational structure, namely RT and RW, Dkm and the Ar-Rahmandan foundation and other local institutional components that are integrated into the Covid-19 RW 24 Task Force by building synergy with the local government, namely Kelurahan and Public health center The presence of the Covid Task Force 19, whose main task was to disseminate and educate health protocols, distribute free masks and establish a Community Granary, for the affected residents to run effectively and have a significant impact when carried out individually by the existing local institutions.